LEARNING TRADITIONS THROUGH THE USE OF “STATIONS” (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The following article is about the study of customs through the method of working at the “Stations”. It is known that the study of traditions on the basis of modern technologies allows you to learn the language of the country and its traditions in a foreign language , to orgonize and conduct an interesting lesson process and to remember them for a long time , at the same time, it also forms in students a respectful attitude towards traditions that are part of national values.